Gender, work, and economy unpacking the global economy - Gottfried, Heidi 1955- (Cambridge, UK Polity Press, 2013)
"This text uses a feminist lens to crack open the often hidden worlds of gender and work, addressing enduring questions about how structural inequalities are produced and why they persist. Making visible the social relationships that drive the global economy, the book explores how economic transformations not only change the way we work, but how we live our lives. The full extent of changing patterns of employment and the current financial crisis cannot be fully understood in the confines of narrow conceptions of work and economy. Feminists address this shortcoming by developing both a theory and a political movement aimed at unveiling the power relations inherent in old and new forms of work. By providing an analysis of gender, work, and the economy, Heidi Gottfried brings to light the many faces of power from the bedroom to the boardroom. A discussion of globalization is threaded throughout the book to uncover the impact of increasing global interconnections, and vivid case studies are included, from industrialized countries such as the US and the global cities of New York, London, and Tokyo, as well as from developing countries and the emerging global cities of Beijing, Shanghai, and Dubai"--Publisher's description.
An introduction to gender, work, and economy : unpacking the global economy -- Theory of work and economy -- An integrative framework for the study of gender, work, and economy -- The puzzle of gender segregation : from historical roots to contemporary divisions -- Serving people : gender and services in the new economy -- Caring for people : gender and social reproduction in service economies -- State and economy : gender, policy, and work -- Terrains of struggle : gender, work, and labor organizing -- Thinking globally, global thinking : theories of internationalization and globalization -- Gender, global labor markets, commodity chains, and mobilities : globalizing production and reproduction -- On the global economic grid : Tokyo tales, London chronicles, Shanghai stories -- New political landscapes : gender equality projects in global arenas and nation states
Includes bibliographical references (pages [294]-320) and indexes
Keywords: Women -- Employment; Sex role in the work environment; Sex discrimination in employment